Changes in Approaches to the Analysis and Forecasting of Domestic Mechanical Engineering within Manufacturing Industries - V. N. Borisov; Yu. V. Zinchenko (Мир новой экономики, 2024)
Relevance: The article analyzes the relationship between the development of domestic mechanical engineering and relevant scientific schools within the framework of the concept of sustainable development. The functioning of domestic mechanical engineering is considered in the context of international associations.   The following methods were applied in the study: a systems approach, functional, comparative economic, and statistical analyses, as well as the authors’ methodological developments.   The scientific novelty of the article lies in the implementation of theauthors’ approach to studying mechanical engineering as an interaction between scientific schools and economic and environmental factors.   The results and conclusions of the study may be useful for decision-making within the existing economic model of the Russian Federation when forecasting, developing, and adjusting strategic programs for industry development.